Polynomial Exact-3-SAT-Solving Algorithm - Mueller, Matthias (International Journal of Engineering and Technology, 2020)
This article describes an algorithm which is supposed by the author to be capable of solving any instance of a 3-SAT CNF in maximal O(n^15), whereby n is the variable index range within the 3-SAT CNF to solve. The presented algorithm imitates the proceeding of an exponential, fail-safe solver. This exponential solver stores internal data in m-SAT clauses, with 3 <= m <= n. The polynomial solver works similarly, but uses 3-SAT clauses only to save the same data. The paper explains how, and proves why this can be achieved. On the supposition the algorithm is correct, the P-NP-Problem would be solved with the result that the complexity classes NP and P are equal.